Classroom Management in Increasing Student Learning Interest - Yulianta, Eka (Institute Of Advanced Knowledge and Science, 2024)
Classroom management is an important component in determining the success of the education process and one of the factors in improving the quality of education in Indonesia. The importance of classroom management makes every educational institution make maximum efforts to meet classroom management standards to improve the quality of the learning process. This research uses a qualitative approach with descriptive analysis. The research subjects were the principal, head of the expertise program and homeroom teacher. The data collection techniques used are the interview method, observation method, and documentation method, which will later obtain primary and secondary data to be analyzed together to draw conclusions. Based on the results of the research that the author has done, it can be concluded that classroom management at SMK Islam Moyudan in supporting the learning process is quite good. However, some classroom management has not been realized, among others, in the process of planning, organizing, maintaining, and supervising classroom infrastructure. The obstacles experienced are the lack of human resources in the field of administration and infrastructure as well as incoming funds for the procurement facility process and the slow infrastructure